Metode Regresi Logistik untuk Menganalisis Pengaruh Profitabilitas Likuiditas, dan Reputasi Auditor terhadap Pelaporan Keuangan Melalui Internet (Internet Financial Reporting) - Wenny Anggeresia Ginting (Owner : Riset dan Jurnal Akuntansi, 2018)
The purpose of this study is to analyze the structure of profitability, liquidity, and Auditor’s Reputationthat affect internet financial reporting. The population is a manufacturing company listed on the Indonesia Stock Exchange, and 75 of them are used as samples, taken using stratified random sampling technique. Data were analyzed by using logistic regression analysis at 5% and 10% significance level to draw conclusion. The results show that, simultaneously, independent variables have an influence on internet financial reporting. Partially, profitability, and auditor's reputation have a positive and significant influence on internet financial reporting. Meanwhile, the liquidity variable has a positive but not significant influence on internet financial reporting Keywords: Profitability, liquidity,andAuditor’s Reputation.